The PADI open water diver video - Professional Association of Diving Instructors (Santa Ana, CA: International PADI Inc., 1991)
Teach the audience about scuba diving. The modules conducted by PADI instructor.
This video consists of 5 modules
Presenter: Dr. Geof Bown
Keywords: Scuba diving